Behaviour of Inelastic Multi-Storey Building Frames Subjected to Strong Ground Motions - Guru, Badri Prasad (My University, 1969)
The theoretical and experimental investigations presented in this thesis are primarily related to the dynamic response of inelastic multi-storey building frames subjected to strong ground motions. The main purpose is to investigate, both analytically and experimentally, those aspects of the dynamic response characteristics which are of importance in aseismic design. In the first part of the thesis, the various parameters pertaining to the structural system are varied in a systematic manner and an assessment is made of the influence of this variation on the maximum response characteristics of the dynamic system. The second part of the thesis consists of an experimental investigation into the inelastic dynamic response of multi-storey frames. The comparison of experimentally obtained inelastic response and that predicted theoretically indicated a good agreement between the two.
Keywords: civil engineering; inelastic; multi-storey; building fram; strong ground motion; aseismic design